Employability Paradox: The Effect of Development Idiosyncratic Deals on Recipient Employees’ Turnover Intention - Zhang, Xiaoyan; Deng, Hui; Xia, Yuhuan; Lan, Yuanyuan (Frontiers in Psychology, 2021)
Applied social cognitive theory, this study built a moderated mediation model to explain how and when development idiosyncratic deals (i-deals) affect recipients’ turnover intention. Specifically, this study proposed two paths that linked development i-deals with the recipients’ turnover intention. One path was a retention path via perceived internal employability and another path was a turnover path via perceived external employability. This study tested the hypotheses with a sample of 337 employees from three companies in China. The results showed that development i-deals improved recipients’ perception of internal and external employability both. Perceived internal employability predicted low risk of turnover, but perceived external employability predicted high risk of turnover. And perceived internal and external employability played mediating roles in the relationship between development i-deals and turnover intention. Furthermore, the recipients’ perception of opportunity to perform in current organization strengthened the relationship between perceived internal employability and turnover intention, but weakened the relationship between perceived external employability and turnover intention. Theoretical and practical implications of these findings were discussed.